Elliptical curve cryptography - Toh, Zheng Yi. (2009)
In cryptography, the aim is to achieve security through encryption and this involves transforming a message also known as plaintext to cipher text via an encryption method. This encrypted message is to be unravelled by legitimate parties that possess certain information called “keys”.